Enantiomeric Separation and Circular Dichroism Detection of Metalaxyl Acid Metabolite by Chiral High Performance Liquid Chromatography - Qiu, Jing; Wang, Qiuxia; Zhou, Zhiqiang; Yang, Shuming (Asian Journal of Chemistry, 2010)
The enantiomers of metalaxyl acid metabolite (MX-acid) were separated by HPLC using cellulose-tris-(3,5-dimethylphenyl-carbamate) (CDMPC) as chiral stationary phase. The effects of mobile phase composition, flow rate and column temperature on the resolution were investigated and good separation was achieved with n-hexane/2-propanol/trifluoroacetic acid as mobile phase. The circular dichroisms detection showed that metalaxyl-acid has similar absorption behaviour to metalaxyl with CD signals reverse to optical rotation direction of S(+)- and R(-)-enantiomer and CD signals of metalaxyl intermediate enantiomers may be reversed with change of CD wavelength.